2021
DOI: 10.3389/fmicb.2021.759196
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Promoter and Coding Regions of Avr3a Cause Gain of Virulence of Phytophthora sojae to Rps3a in Soybean

Abstract: Phytophthora sojae threatens soybean production worldwide, and the cultivation of soybean cultivars carrying Rps genes is the most effective way to control this pathogen. However, DNA mutations in the Avr genes of P. sojae can escape recognization of the corresponding Rps genes, leading to the loss of soybean resistance. In this study, we investigated sequence polymorphism and transcript level of the Avr3a gene in Chinese isolates of P. sojae. Twenty-four mutations resulting in five unique Avr3a alleles were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Phytophthora sojae pathotype composition within populations is thought to evolve and change over time due in part to the selective pressure of always planting soybean varieties containing the same Rps gene each rotation 10 . A P. sojae population adapts due to this constant selective pressure from the host through mechanisms such as outcrossing with other P. sojae genotypes 59 , as well as mutations 60 , 61 or gene-silencing 62 of the detected P. sojae Avr -gene product. If the soybean Rps gene is unable to detect infection by P. sojae , no defense response is activated; the plant is therefore susceptible to infection, and disease ensues.…”
Section: Resultsmentioning
confidence: 99%
“…Phytophthora sojae pathotype composition within populations is thought to evolve and change over time due in part to the selective pressure of always planting soybean varieties containing the same Rps gene each rotation 10 . A P. sojae population adapts due to this constant selective pressure from the host through mechanisms such as outcrossing with other P. sojae genotypes 59 , as well as mutations 60 , 61 or gene-silencing 62 of the detected P. sojae Avr -gene product. If the soybean Rps gene is unable to detect infection by P. sojae , no defense response is activated; the plant is therefore susceptible to infection, and disease ensues.…”
Section: Resultsmentioning
confidence: 99%
“…The silence is due to an insertion of a transposon-like fragment in its promoter region ( Qutob et al, 2009 ). Promoter and 5′-UTR sequence analysis revealed eight unique mutations in the promoter region of PsAvr3a , providing new insights into the escape mechanisms of P. sojae ( Hu et al, 2021 ). Further studies revealed that the virulence of PsAvr3a is also associated with the accumulation of small RNA.…”
Section: Destruction Of Transcription Elementsmentioning
confidence: 99%